Islamic Educational Values in the Implementation of the Cambuk Lidi Ceremony (Study of Derati Village Kota Padang District) - Mirzon Daheri; Cica Dwi Julianti (Journal of Contemporary Islamic Education, 2023)
Tradition is a habit passed down from time to time across generations. Each tradition has values useful for maintaining life personally and socially, including the Cambuk Lidi tradition in Derati Village, Kota Padang District, Rejang Lebong, Indonesia. Researchers explore its values by conducting observations, interviews, and documentation. Interviews were conducted with community leaders, namely the chairman and members of the Badan Musyawrah Adat (BMA), religious officials, village officials, and perpetrators who were sentenced to Cambuk Lidi (people who had been Cambukped). The results show that at least two important values are contained in this tradition, namely the values of faith and moral values. The value of faith is to believe and carry out all His commands. The moral value of Cambuk Lidi is to build a responsible attitude, have a sense of shame and immediately correct themselves from mistakes.